MIS management information systems - Bidgoli, Hossein (Cengage Learning, Inc., 2021)
Introduce your students to MIS today with the most practical and current title available: MIS 10. Updates throughout this edition present the latest developments in cloud computing, AR/VR, quantum computing and blockchain. New case studies and information boxes connect the principles your students are learning to the most current developments in technology and business today. Key concepts and skills within each case are now tagged to the corresponding AASCB standards to ensure your students are focused on the most important information for success. For further support, this edition's completely redesigned MindTap offers a robust digital learning experience. New MindTap concept and career videos present job options while interactive case studies bridge today's technology and strategy. Use It activities, give your students immediate feedback and MindTap's RSS feeds present the latest trends with a focus on success in the real world.